Dual-View Integral Imaging System With Wide Viewing Angle And High Spatial Resolution - Huan Deng; Sai Li; Lei Wang; Yan Xing; Qiong-Hua Wang (IEEE Photonics Journal)
In this paper, a dual-view integral imaging system is proposed to present two different 3D images for viewers in different viewing zones. For most of the conventional dual-view integral imaging systems, either the viewing angle or the spatial resolution of 3D image is decreased. In the proposed dual-view system, the viewing angle of each viewing zone is enlarged by introducing a switchable mask. Meanwhile, the spatial resolution of the 3D image is maintained by using the time-division multiplexing technology. A prototype of the proposed dual-view system is developed and it has wide viewing angle and high spatial resolution. The experiments coincide with the theoretical analysis.